Stability of the Intrinsic Motivation Inventory (IMI) for the use of Malaysian form one students in ICT literacy class. - Eow, Yee Leng; Wan Ali, Wan Zah; Baki, Roselan; Mahmud, Rosnaini (EURASIA, 2010)

(untitled)
The objective of the study is to determine the suitability of the Intrinsic Motivation Inventory (IMI) in assessing Malaysian form one students’ intrinsic motivation gained through the tasks engagement in Information and Communication Technology (ICT) literacy class. 236 students completed the IMI in Bahasa Malaysia version. The reliability value of Cronbach Alpha for intrinsic motivation as a whole was .844. Cronbach Alpha values for the dimensions within IMI were in the range of .560 to .932. The two factors solution extracted from the factor analysis represented 66.85 percent of the total variance. All the dimensions in the initial IMI instrument were included in the two factors solution. Out of the 34 items, only item 13 was deemed to be unreliable as the factor loading generated was very low. The findings were further confirmed by using two incremental fit measurements, Tucker-Lewis Index and Normed Fit Index, generating values of .985 and .994 respectively. Although there were a few limitations in the study, researchers are cautiously optimistic that the findings will be both valuable and applicable for the assessment of intrinsic motivation gain through the ICT literacy class among Malaysian form one students.